2016
DOI: 10.1021/acsphotonics.5b00710
|View full text |Cite
|
Sign up to set email alerts
|

Nanofocused Plasmon-Driven Sub-10 fs Electron Point Source

Abstract: Progress in ultrafast electron microscopy relies on the development of efficient laser-driven electron sources delivering femtosecond electron pulses to the sample. In particular, recent advances employ photoemission from metal nanotips as coherent point-like femtosecond low-energy electron sources. We report the nonlinear emission of ultrashort electron wave packets from a gold nanotip generated by nonlocal excitation and nanofocusing of surface plasmon polaritons. We verify the nanoscale localization of plas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
105
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 65 publications
0
105
0
1
Order By: Relevance
“…Since our first implementation of such a plasmon nanofocusing electron source [87], related work has also been reported in Refs. [88,90].…”
Section: Plasmon Nanofocusing For Ultrafast Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Since our first implementation of such a plasmon nanofocusing electron source [87], related work has also been reported in Refs. [88,90].…”
Section: Plasmon Nanofocusing For Ultrafast Electron Microscopymentioning
confidence: 99%
“…When coupling ultrafast laser pulses to propagating SPPs at the shaft of those tapers, nanometre-localized light spots with pulse durations as short as 10 fs are created at the taper apex with high efficiency [42,76]. Consequently, the optical properties of such antennas have been studied in considerable detail, both experimentally and theoretically, during the past several years [42,63,64,70,[75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91].…”
Section: Introductionmentioning
confidence: 99%
“…The progress in the field of nanophotonics has been fueled by advances in fabrication techniques such as lithography 1,2 and chemical synthesis, 3 where optical properties of nanomaterials are used to achieve functionality. 4,5 Collective electron motion as a result of the interaction of ultrashort light pulses with nanomaterials typically unfolds on attosecond to femtosecond time scales, where its properties depend on the waveform of the laser field, 6 and the material, composition, 7 shape, 8 and configuration 2 of nanomaterials, and their local environment.…”
Section: Introductionmentioning
confidence: 99%
“…16 The photoemission from metal nanotips is of particular interest offering the possibility to produce ultrashort electron pulses. These in turn can be used to seed electron accelerators, 17,18 and as an electron source for transmission 19 and diffraction imaging studies, 1 offering Angstrom spatial and down to attosecond temporal resolutions. It was recently found that the electron emission from metallic nanotips can be controlled with the carrier-envelope phase (CEP) of few-cycle laser pulses in the single-electron emission regime.…”
Section: Introductionmentioning
confidence: 99%
“…The ultrafast nature of the adiabatic concentration has been used to achieve simultaneously nanoscopic spatial resolution and femtosecond temporal resolution [19][20][21][82][83][84][85][86][87][88][89]. A unique application of the adiabatic nanofocusing is a new type of nanoscopy with chemical vision based on a highly efficient (with a quantum yield of 10%) hot electron generation [90].…”
Section: Adiabatic Nanofocusing and Sersmentioning
confidence: 99%